PS-015 The development of a video to demonstrate extemporaneous eye drop preparation for use by community pharmacists. (25th February 2017) - Molony, S; Field, C; Creed, M; Brown, J; Meegan, C
Abstract : Background: The hospital is a tertiary ophthalmology referral centre. Extemporaneous eye drops are required to treat acute ophthalmic conditions when a commercial alternative is not available. Due to the specialised nature of these ophthalmic preparations, the critical need of the patient, short shelf-life and the geographical dispersion of the patients, often extemporaneous preparation is the only option. The ophthalmology pharmacist provides community pharmacies with aseptic preparation guidelines and eye drop protocols for patients on discharge. Additionally, the pharmacist fields calls in relation to the preparation of these drops. Anecdotally, community pharmacists find the preparation of eye drops a complicated process, leading to fear of undertaking a procedure not routinely practiced. Purpose: To aid the discharge process for patients on extemporaneous eye drops. Material and methods: A survey of 13 community pharmacists who had been asked to prepare extemporaneous eye drops over 3 months was undertaken to determine if the development of a video was a helpful initiative. Pharmacy stakeholders met to agree the inclusion material. The 'biomedical imaging department', agreed to film the video. A pharmacy technician and the ophthalmology pharmacist researched the process and split the process into individual steps. A story board was drafted and presented to clinical photography. The video was reviewed by pharmacy management and further amended. A link to the video was emailed to community pharmacies as was required. The video was also hosted on the website of a national pharmacy professional development organisation. Results: All 13 community pharmacists surveyed felt that a video demonstrating extemporaneous preparation of eye drops would be a useful reference tool. The video was developed for dissemination to community pharmacists. Conclusion: It is envisioned that the development of this innovative tool will aid community pharmacists when extemporaneous eye drops are required to treat acute ophthalmological conditions. The video was developed to complement existing written material provided. It will be disseminated to community pharmacies via an email link and has been hosted on national pharmacist education websites. There is also potential for future dissemination on video sharing sites. References and/or acknowledgements: We are grateful to the hospital biomedical imaging department for filming the video. No conflict of interest